Evaluation of Basic Emergency Obstetric and Newborn Care (BEMONC) Implementation (Unnes Journal of Public Health, 2019)
Abstract Maternal Mortality Rate is one indicator in describing the health status of people in a region. This study aimed to evaluate the implementation of Basic Emergency Obstetric and Newborn Care (BEMONC) at the Tegalrejo Yogyakarta Public Health Center with Basic Emergency Obstetric and Newborn Care. This research was qualitative with a case study design. The subjects were 5 BEMONC Core Team informants and 3 BEMONC patients. The instrument used in-depth interviews and checklists. The results of the Input: do not have nurses in the BEMONC core Team, due to a lack of nurses and not all BEMONC officers have received training. Infrastructure facilities were insufficient, but budget was enough. The BEMONC implementation went well but on holydays the doctors did not stand by and the shift was not evenly distributed. The implementation output reached the target and the service was satisfactory but found officers who were not friendly with the patient's family. Input is in accordance with the standard, but health personnel and training are not up to standard. The output reached the target and the service was satisfactory but one of the officers was not friendly. The Team must try to focus on customer satisfaction in a friendly manner so that the services provided meet patient expectations. Abstrak Angka Kematian Ibu merupakan salah satu indikator dalam menggambarkan derajat kesehatan masyarakat di suatu wilayah. Penelitian ini bertujuan untuk mengevaluasi pelaksanaan Pelayanan Obstetri Neonatal Emergensi Dasar (PONED) di Puskesmas PONED Tegalrejo Yogyakarta. Penelitian ini adalah kualitatif dengan rancangan studi kasus. Subyek sebanyak 5 informan Tim Inti PONED dan 3 pasien PONED. Instrumen menggunakan wawancara mendalam dan checklist. Hasil pada Input tidak terdapat perawat di dalam Tim inti PONED, disebabkan kurangnya perawat dan belum semua petugas PONED mendapatkan pelatihan. Sarana prasarana kurang tercukupi namun pendanaannya tercukupi. Pelaksanaan PONED berjalan baik namun pada hari-hari besar dokter tidak stand by dan pembagian shift kurang merata. Output pelaksanaan mencapai target dan pelayanannya memuaskan namun ditemukan petugas yang kurang ramah dengan keluarga pasien. Input sesuai dengan standar, namun tenaga kesehatan dan pelatihan tidak sesuai standar. Output mencapai target dan pelayanan yang memuaskan namun salah satu petugasnya kurang ramah. Sehingga Tim harus berusaha fokus terhadap kepuasan pelanggan secara ramah agar pelayanan yang diberikan memenuhi harapan pasien.